2005
DOI: 10.1002/cncr.20887
|View full text |Cite
|
Sign up to set email alerts
|

Levels of angiogenesis and expression of angiogenesis‐related genes are prognostic for organ‐specific metastasis of renal cell carcinoma

Abstract: BACKGROUND.To identify organ-specific, metastasis-related factors that can be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 40 publications
2
48
0
1
Order By: Relevance
“…Smaller studies by others have shown variable associations between clinical outcome and microvessel density. 10,20 Kurban et al 6 showed that VHL mutations resulting in upregulation of HIF1a are associated with decreased microvessel density and low invasive potential, consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Smaller studies by others have shown variable associations between clinical outcome and microvessel density. 10,20 Kurban et al 6 showed that VHL mutations resulting in upregulation of HIF1a are associated with decreased microvessel density and low invasive potential, consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Other smaller studies assessing VEGF/VEGF-Rs and microvessel density have been conducted. [9][10][11] Jacobsen et al 12 assessed a relatively large cohort tissue microarray (TMA) for VEGF expression, but no assessment of VEGF-R expression and microvessel density was made. Our purpose was to assess expression of VEGF, VEGF-R1, VEGF-R2 and VEGF-R3 in three tissue components: RCC cells, endothelial cells and adjacent normal renal tissue on a large patient cohort with associated clinical/ pathological data.…”
mentioning
confidence: 99%
“…Most, though not all, clinical studies demonstrate a direct correlation of high primary tumor blood microvessel densities (MVDs) with increased incidence of metastases [150,151]. Tumor MVD is a significant and independent prognostic indicator for relapse-free and overall survival of cancer patients [152].…”
Section: Tumor Angiogenesismentioning
confidence: 99%
“…[7] FGF/fibroblast growth factor receptor (FGFR) signaling promotes vascularization (vessel assembly, sprouting and branching), lymphangiogenesis and cellular growth in several human malignancies, [8][9][10] including RCC. [11] Interestingly, increased basic-FGF plasma concentrations correlate with high tumor grade and stage, [12] metastatic spreading [13] and poor prognosis [14] in kidney cancer patients. Moreover, FGF serum levels significantly increase in mRCC patients with disease progression while receiving sunitinib therapy, supporting the potential FGF-pathway role as a potent mediator of endothelial cell resistance to VEGFR inhibitors.…”
Section: Introductionmentioning
confidence: 99%